The Influence of Powtoon-Assisted Group to Group Exchange and Powtoon-Assisted Talking Chips Learning Models in Primary Schools - Achmad Buchori; Nyai Cintang (International Journal of Evaluation and Research in Education (IJERE), 2018)
The element of creativity in learning mathematics in elementary school is lack of attention. Whereas, in solving the mathematic problem, creative thinking and ideas are needed in formulating and solving mathematical models of mathematic problems. Creative thoughts and ideas will emerge and develop if the process of learning mathematics in the classroom uses appropriate learning approach. The purpose of this study is to determine the influence of students' mathematical creative thinking ability on Powtoon-Assisted Group to Group Exchange and Talking Chips learning models to students' creative thinking ability. This research is a correlative quantitative research. The population was all the sixth grade students of Pedurungan Tengah 1 State Primary School in Semarang. The samples were class VI C (experiment 1), VI D (experiment 2), and VI B (control). The data were obtained from a post-test with open-ended answers. The analysis result of Anava test indicated that there was a difference on the mean of students' creative thinking ability in those three classes. Based on the Scheffe Test calculation, students' mathematical creative thinking ability with GGE model was better than the class with conventional learning model. Another result of Scheffe Test calculation indicated that students' mathematical creative thinking ability with Talking Chips model was better than the class with conventional learning. In addition, the Simple Linear Regression equation in both classes with GGE and Talking Chips models resulted in positive value equation. It could be concluded that Powtoon-Assisted Group to Group Exchange and Talking Chips learning models have a positive influence on students' creative thinking ability.